PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING BERBASIS E-LEARNING DAN ADVERSITY QUOTIENT TERHADAP KEMAMPUAN BERPIKIR KREATIF SISWA PADA MATA PELAJARAN EKONOMI : THE INFLUENCE OF E-LEARNING-BASED PROBLEM LEARNING LEARNING MODELS AND ADVERSITY QUOTIENT ON STUDENTS' CREATIVE THINKING SKILLS IN ECONOMICS SUBJECTS - Hilda Fitria; Siti Nurjanah; Ari Saptono (Yayasan Education and Social Center, 2023)
The aim of this research was to develop students' creative thinking skills through the E-Learning-Based Problem Based Learning model and the Adversity Quotient abilities of students at the high school level in Economics. The method used in this study is the experimental method with a 2x2 factorial design. The population of this study were all students at SMA Negeri 83 Jakarta Utara and SMA Negeri 52 Jakarta Utara. The sample of this study was students of class XI IPS 1 and XI IPS 2 at each school, where class XI IPS 1 was used as the control class and XI IPS 2 as the experimental class. The research instruments used were questionnaires and pre-test post-test questions. The results of data analysis using two-way ANOVA revealed that there were differences in students' creative thinking abilities between conventional classes and E-learning-based PBL classes, there were differences in students' creative thinking abilities between low and high AQ, there was interaction between learning models and AQ on creative thinking abilities, there was differences in creative thinking abilities between conventional classes and e-learning based PBL classes for high AQ students, there are differences in creative thinking abilities between conventional classes and e-learning based PBL classes for low AQ students, there are differences in creative thinking abilities in conventional classes between AQ students high and low and there are differences in the ability to think creatively in e-learning-based PBL classes between high and low AQ students